Is president above the constitution? - a discussion in the background of recent constitutional crisis in - Kosalai, M. (University of Jaffna, 2019)
The Constitution of 1978 introduced the Executive Presidential system for the first time in Sri Lanka. The Executive President is vested with wider powers including the power to appoint and remove the Prime Minister. However the 19th Amendment to the Constitution diminished the Executive President’s power to a considerable amount thereby the power of the president to remove the Prime Minister is subject to lawful limitations. The constitutional restrictions on the removal of Prime Minister from the post have been attacked severely with the appointment of former President MahindaRajapaksa as the new Prime Minister while sacking the incumbent RanilWickremesinghe, by the Executive President MaithripalaSirisena on 26th October 2018. Subsequently the President MaithripalaSirisena dissolved the Parliament. With the appointment of a new Prime Minister, and the dissolution of Parliament a constitutional crisis arose and people are skeptical as to whether the President is placed above the Constitution in Sri Lanka. This paper focuses only on the constitutionality of the appointment of new Prime Minister on 26 October 2018. The objective of the research is to analyze the constitutionality of the appointment of Hon.MahindaRajapaksa as the Prime Minister and its impact on the principles of constitutionalism, rule of law, democracy and good governance. To this end a qualitative research is carried out, the relevant constitutional provisions, the judicial determinations and the opinion expressed by different stake holders over the matter are dealt with in much detail.
Keywords: executive presidency; prime minister; appointment; Removal; constitutionality; rule of law